Clinic immunological comparison when studying erosive affections of gastro duodenal zone in patients with bronchial asthma - G. M. Chernyavskaya; E. I. Beloborodova; T. V. Perevozchikova; R. A. Pozdnyakov; E. A. Fait; S. D. Degtyarev (Бюллетень сибирской медицины)
The aim of the work is to study the condition of the local immunity of stomach when there is bronchial asthma and the role of affection of some its factors in the formation of gastro duodenal pathology in this category of patients. 302 patients, both male and female were examined in the age of 18—60 with exogenous and mixed bronchial asthma. Gastro duodenal zone of all patients and local immunity of stomach in 65 patients were examined. The condition of the local immunity of the stomach was evaluated according to the content of secretory antibody A (sIgA), antibody G (IgG), circling immune complexes, activity of lysozyme in stomachic secretion. 68 patients (22,5%) have erosive affections of gastro duodenal zone. It is revealed that pathology of gastro duodenal zone is developed with the local deficit sIgA and rise of the content IgG in stomachic secretion. Dose-dependent effect of the long term peroral therapy by the systematic glucocorticosteroids at bronchial asthma on the pathology of gastro duodenal zone and local immunity of the stomach is revealed. Lowering the content of IgG and circling immune complexes in stomachic secretion and immune complex reactions in mucous membrane of the stomach, physiological doses lower the frequency of erosive affections of gastro duodenal zone. Treatment by supraphysiological doses of systematic glucocorticosteroids brings on disruption of specific protection section in mucous membrane of the stomach. It leads to the rise of erosive affections of gastro duodenal zone in this category of patients. Revealed affections of the local humoral immunity of the stomach in the patients have general characteristics and one-directed character of changes with the local immunity of respiratory tract when there is bronchial asthma. It gives the opportunity to suppose the participation of immune system of mucous membrane when having bronchial asthma.